2020
DOI: 10.1080/13880209.2020.1803368
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of the traditional Chinese medicine formula Qing-Mai-Yin on arteriosclerosis obliterans in a rabbit model

Abstract: Context Qing-Mai-Yin (QMY) is a clinically used herbal formula for treating arteriosclerosis obliterans (ASO). Objective To evaluate the chemical constituents and effects of QMY on ASO rabbit model. Materials and methods Forty-eight New Zealand rabbits were divided into six groups ( n = 8): normal (normal rabbits treated with 0.5% CMC-Na), vehicle (ASO rabbits treated with 0.5% CMC-Na), positive (simvastatin, 1.53 mg/kg),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…All MS experiments were conducted on the Full MS-ddMS2 model with negative and positive scan modes, and the mass scan range was m/z 100–1200. The original raw mass spectra were extracted using Compound Discover 3.2 software, and data analysis was carried out by using the online database, mzCloud, and the self-constructed local database, mzVault ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…All MS experiments were conducted on the Full MS-ddMS2 model with negative and positive scan modes, and the mass scan range was m/z 100–1200. The original raw mass spectra were extracted using Compound Discover 3.2 software, and data analysis was carried out by using the online database, mzCloud, and the self-constructed local database, mzVault ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that HZQMF can improve vascular function through its anti-inflammatory and anti-oxidative effects. [9,10] However, the underlying therapeutic mechanisms remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…2 Besides, a TCM formula usually comprises several herbs, mostly herbal, but sometimes mineral and animal-derived. 3–5 Mai-Luo-Shu-Tong pill (MLSTP) is an effective TCM formula for the treatment of superficial thrombophlebitis. 6,7 It is composed of 12 TCMs including Astragali Radix, Lonicerae Japonicae Flos, Phellodendri Chinensis Cortex, Atractylodis Rhizoma, Coicis Semen, Scrophulariae Radix, Angelicae Sinensis Radix, Paeoniae Radix Alba, Glycyrrhizae Radix Et Rhizoma, Hirudo, Scolopendra and Scorpio.…”
Section: Introductionmentioning
confidence: 99%